Condition assessment model for sewer pipelines using fuzzy-based evidential reasoning. Issue 1 (2nd January 2018) - Hawari, Alaa; Alkadour, Firas; Elmasry, Mohamed; Zayed, Tarek
Abstract: A condition assessment model for gravity and pressurised sewer pipelines using Fuzzy Set Theory (FST), and Evidential Reasoning (ER) with the aid of Fuzzy Analytical Network Process (FANP) integrated with Monte-Carlo Simulation is presented in this paper. Seventeen factors were considered for gravity pipelines in addition to the operating pressure for pressurised pipelines. The model was developed using relative weights for the different factors affecting pipelines condition which were obtained using FANP integrated with Monte-Carlo Simulation based on the results of a questionnaire that was distributed to experts working in the field of infrastructures. FST was used to set thresholds for the different effect values of factors on the pipelines' condition, whereas ER was used to determine the final condition assessment index for the pipeline by aggregating both the relative weights and effect values for the different affecting factors.